1999
DOI: 10.1016/s0194-5998(99)70323-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Rates of Salivary Gland Tumors: Results from a Population‐Based Study

Abstract: Salivary gland tumors are uncommon, and their epidemiology has not been well described. We conducted a descriptive epidemiologic study of parotid, submaxillary, and sublingual gland tumors newly diagnosed in Jefferson County, Alabama, hospitals from 1968 to 1989. Incidence rates were estimated with a population-based subset of cases diagnosed during the years 1979 to 1980, 1983 to 1984, or 1987 to 1988. Among 248 incident cases, 84.3% were benign and 15.7% were malignant. Eighty-six percent of cases arose in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

28
265
7
32

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(332 citation statements)
references
References 18 publications
28
265
7
32
Order By: Relevance
“…Malignant tumors of major salivary glands are rare and represent only 3%-6% of all head and neck (Pinkston and Cole, 1999) cancers (Spiro, 1986). Around 80% of salivary gland tumors arise from parotid gland of which 20-30% are malignant (Matsuba et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumors of major salivary glands are rare and represent only 3%-6% of all head and neck (Pinkston and Cole, 1999) cancers (Spiro, 1986). Around 80% of salivary gland tumors arise from parotid gland of which 20-30% are malignant (Matsuba et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Of all the salivary gland neoplasms, 85% are benign and 15% are malignant. Salivary gland malignancies comprise 3-6% of all head and neck cancers (Pinkston and Cole, 1999;Jones et al, 2008). It constitutes 0.77% of male and 0.57% of female cancers in India (Raina et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have provided valuable knowledge, some of the data become contradictory and less precise as SGT classifications continue to change. As such, the actual frequency of SGTs is not known, and it is probably underestimated because benign tumors, which constitute the majority of SGTs, are often not entered into most cancer registries [12]. A comprehensive comparison of the studies reported from different parts of the world is hampered by several reasons, as summarized by Buchner et al [7].…”
Section: Introductionmentioning
confidence: 99%